(untitled) (diségno, 2019)
Lands depending on the Royal Site of Aranjuez have undergone several transformations throughout the last five centuries. Their particular geographic features together with the traces related to the historic uses in the ser vice of the King’s leisure –but also to a secular agriculture, livestock and hunting exploitation– were shown in an interesting set of maps, plans, paintings and drawings. Ancient cartography still permits to locate the main geographic landmarks, and also the constructions built throughout the territories and the centuries, paying a special attention to the neighboring town and its development. In turn, pictures and drawings depict some particular performances that were supported by a set of more or less ephemeral buildings and traces. An exhaustive fieldwork permitted us to check their state of preservation, and to analyze the lasting remains of historic uses and forms.